Socioeconomic and productive characterization of native bean producers in Guerrero - Espinosa-Rodríguez , Mariana; Sabino-López, Juan Elías; Antúnez-Ocampo, Oscar Martín; Pérez-Pacheco, Rafael; Maldonado-Peralta, María de los Ángeles (Revista Mexicana de Ciencias Agrícolas, 2025)
Beans (Phaseolus vulgaris L.) are important in the Mexican diet; they are grown in all regions of Mexico in 1 690 000 ha, with a production of 1 289 000 t and per  capita consumption of 11 kg. Guerrero is the sixth largest bean producing state nationwide with 27 014 producers and a production of 11 155 t. The objective was the socioeconomic and productive characterization of native bean producers from nine localities in three regions of Guerrero, Mexico. An interview with questions about social, economic, and production variables was applied to 117 bean producers from nine communities in three regions (North, Central, and Mountain) of Guerrero, Mexico. A cluster analysis was applied to the data collected, using factor analysis for the selection of variables and defining the hierarchical cluster with Ward’s method and the Euclidean distance, resulting in seven groups of producers. Sixty-three point two percent of producers are men, 62.4% have an elementary level of education, 17% speak an indigenous language, the average age was 48 years, and 59.8% use family labor for bean cultivation. Agriculture is their main economic activity, with 22 years of experience in this crop, planted on 0.8 ha with an average yield of 250 kg ha-1. The results contribute to identifying the problems regarding the production process, postharvest management, and sales, as well as the actors that limit bean productivity, putting at risk its long-term conservation in some communities of Guerrero, Mexico.
Keywords: commercialization; communities; conservation; production